Comparison of longterm outcomes and quality of life in recipients of donation after cardiac death liver grafts with a propensity‐matched cohort. Issue 3 (March 2017) - Croome, Kristopher P.; Lee, David D.; Perry, Dana K.; Burns, Justin M.; Nguyen, Justin H.; Keaveny, Andrew P.; Taner, C. Burcin
Abstract : The use of liver grafts from donation after cardiac death (DCD) has been limited due to the increased rate of graft failure, mostly related to ischemic cholangiopathy (IC). It is our hypothesis that longterm outcomes and quality of life (QOL) similar to patients undergoing liver transplantation (LT) with donation after brain death (DBD) can be achieved. Clinical outcomes of all patients undergoing DCD LT (n = 300) between 1998 and 2015 were compared with a propensity score–matched cohort of patients undergoing DBD LT (n = 300). Patients were contacted for a follow‐up questionnaire and short‐form (SF)–12 QOL Survey administration. Median follow‐up was >5 years. Graft survival at 1‐, 3‐, and 5‐years was 83.8%, 75.5%, and 70.1% in the DCD LT group and 88.4%, 80.3%, and 73.9% in the DBD LT group ( P = 0.27). Patient survival at 1‐, 3‐, and 5‐years was 92.3%, 86.1%, and 80.3% in the DCD LT group and 92.3%, 85.1%, and 79.5% in the DBD LT group ( P = 0.81). IC developed in 11.7% and 2% of patients in the DCD LT group and DBD LT group, respectively ( P < 0.001). DCD LT recipients who developed IC had inferior graft survival compared with both the DCD non‐IC group ( P < 0.001) and the DBD LT group ( P < 0.001); no difference in graft survival was observed between the DCD non‐IC group and the DBD LT group ( P = 0.50). Physical and Mental Composite Scores on the SF‐12 QOL questionnaire were similar between the DCD LT and DBD LT groups (44.0 versus 45.4; P = 0.34 and 51.9 versus 52.2; P = 0.83), respectively. Similar longterm survival and QOL scores can be achieved between DCD LT and DBD LT. Prevention of IC in DCD LT yields excellent graft and patient survival with virtually no difference compared with DBD LT. Liver Transplantation 23 342–351 2017 AASLD .